Improving the Technical Characteristics of AESA Pulse Radars by Reducing the Power Consumption Droop of Transmitting Modules - N. A. Kushnerev; M. V. Rodin; D. O. Popov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. When shaping radar signals, the transmission paths of pulsed radars with active electronically scanned arrays (AESA) frequently use a periodic charge/discharge of capacitive energy storage devices. In such cases, the power amplifier of the transmitting module consumes electricity over short time intervals. However, the pulsed nature of the amplifier operation causes uneven power consumption of the storage charger. This leads to a deterioration in the electromagnetic compatibility of radar equipment and a decrease in operation reliability due to the additional load on the power supply system. To reduce the unevenness of power consumption, smoothing choke сoils are used together with storage devices, which degrade the weight–size characteristics and the entire performance of the radar. Thus, the task of reducing the uneven power consumption droop of transmitting modules without compromising their weight–size characteristics appears relevant.Aim. To demonstrate the possibility of constructing a charger for a capacitive storage device that ensures uniform power consumption of the transmitting module due to constant charge power, with the purpose of improving a number of technical characteristics of the AESA.Materials and methods. A review of methods for charging capacitive storage devices and an analysis of the possibility of constructing a charger for a storage device with constant power using the theory of electrical circuits. The operation of a constant-power charger was analyzed in the Micro-Cap environment and using its experimental prototype, taking the actual durations and frequencies of radar signals into account.Results. A new charger for a capacitive storage device with constant power is proposed and the principle of its operation is considered. A simulation model and an experimental prototype are developed, which confirmed the possibility of significantly reducing the power consumption droop of the AESA transmitting module without the use of bulky smoothing chokes. Directions for further improvement of the charger are outlined.Conclusion. The proposed 120-W capacitor storage charger for the radar AESA transmitting module is characterized by simplicity of implementation and a high energy efficiency of the charge. This charger can be recommended for use in advanced radars with AESA for the purpose of improving a number of technical characteristics.